Experiences and Risk Factors Associated with Transactional Sex Among Men Who Have Sex with Men: A Qualitative Study in Medan, Indonesia Implications for HIV Prevention and Sexual Health Interventions - Risydah Fadilah; Sari Atika Parinduri; Nisfi Balqish Rusli (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Transactional sex between men carries a high risk of transmitting sexually transmitted infections. This study employed a qualitative phenomenological approach through in-depth interviews with homosexual men engaged in transactional sex. Inclusion criteria included men aged 19–40 who were sexually active with heterosexual, homosexual, or bisexual partners. Participants were adults at the time of recruitment but some reported having hinitiated sexual intercourse during adolescence (as early as age 13), reflecting on their earlier experiences. Data were obtained through observation and semi-structured interviews lasting 60–100 minutes per session. Data analysis was conducted in three stages: data reduction, data presentation, and verification. The results showed that multiple partners, a large number of partners, and the lack of personal protective measures, particularly condom use, were dominant factors that increased the risk of transmission and spread of sexually transmitted infections. Furthermore, transactional sex tended to occur without long-term commitment, thus reinforcing risky behavior patterns. These findings emphasize the importance of condom availability and use as primary prevention measures to reduce the risk of infection. This study highlights the urgency of education-based prevention strategies and health promotion for men who engage in same-sex sex. Therefore, increasing awareness about safe sex behavior is a crucial step in reducing vulnerability to sexually transmitted infections among this high-risk group.